Fluorescent probe sensor based on (R)‐(−)‐4‐phenyl‐2‐oxazolidone for effective detection of divalent cations. (8th June 2020) - Baruah, Shyamal; Aier, Merangmenla; Puzari, Amrit
Abstract: Significant progress attained in sensor science in recent years has resulted in the development of highly efficient fluorescence probes for sensing metal ions. Fluorescent molecular probes based on (R)‐(−)‐4‐phenyl‐2‐oxazolidone are reported here. Fluorescence studies indicated that the molecular probe could be used successfully to sense divalent metal cations such as Cu 2+, Co 2+, Pb 2+, and Zn 2+ . The addition of divalent metal cations to the molecular probe produced a specific interaction pattern under UV–visible and fluorescence spectroscopy. These molecules could detect metal cations using fluorescence quenching. Stern–Volmer plots were used to determine quenching rate coefficients, which were calculated to be 2 × 10 1, 1.06 × 10 3 and 7.39 × 10 2 M −1 s −1 for copper, cobalt, and zinc respectively. Calculation of limit of detection for heavy metal cations revealed that the reported molecular probes improved the limit of detection compared with available standard data. Limit of quantitation values were also well within the permissible range. The frontier energy gap of highest occupied molecular orbital to the lowest unoccupied molecular orbital was evaluated using the density functional theory approach and Gaussian 09 W software, which complemented the coordination of azetidinones with divalent metal ions.